The unbearable weight of massive talent [videorecording (Blu-Ray + DVD)] - Gormican, Tom, 1980-; Etten, Kevin; Cage, Nicolas, 1965-; Nilon, Mike, 1967-; Pascal, Pedro; Harris, Neil Patrick, 1973-; Haddish, Tiffany, 1979-; Isham, Mark; Bluck, Nigel (Lionsgate, 2022)
A cash-strapped Nicolas Cage agrees to make a paid appearance at a billionaire mega fan's birthday party, but is really a snitch for the CIA since the billionaire fan is a drug kingpin and gets cast in a Tarantino movie.